Acute Exercise in Hypobaric Hypoxia Attenuates Endothelial Shedding in Subjects Unacclimatized to High Altitudes - Kröpfl, Julia M.; Kammerer, Tobias; Faihs, Valentina; Gruber, Hans-Jürgen; Stutz, Jan; Rehm, Markus; Stelzer, Ingeborg; Schäfer, Simon T.; Spengler, Christina M. (Frontiers in Physiology, 2020)
Travel of unacclimatized subjects to a high altitude has been growing in popularity. Changes in endothelial shedding [circulating endothelial cells (ECs)] and hematopoietic stem and progenitor cells (CPCs) during physical exercise in hypobaric hypoxia, however, are not well understood. We investigated the change in ECs and CPCs when exposed to high altitude, after acute exercise therein, and after an overnight stay in hypobaric hypoxia in 11 healthy unacclimatized subjects. Blood withdrawal was done at baseline (520 m a.s.l.; baseline), after passive ascent to 3,883 m a.s.l. (arrival), after acute physical exercise (±400 m, postexercise) and after an overnight stay at 3,883 m a.s.l. (24 h). Mature blood cells, ECs, and CPCs were assessed by a hematology analyzer and flow cytometry, respectively. The presence of matrix metalloproteinases (MMPs), their activity, and hematopoietic cytokines were assessed in serum and plasma. EC and CPC concentrations significantly decreased after exercise (p = 0.019, p = 0.007, respectively). CPCs remained low until the next morning (24 h, p = 0.002), while EC concentrations returned back to baseline. MMP-9 decreased at arrival (p = 0.021), stayed low postexercise (p = 0.033), and returned to baseline at 24 h (p = 0.035 to postexercise). MMP-activity did not change throughout the study. Circulating MMP-9 concentrations, but not MMP-activity, were associated with EC concentrations (rrm = 0.48, p = 0.010). CPC concentrations were not linked to hematopoietic cytokines. Acute exercise at high altitude attenuated endothelial shedding, but did not enhance regenerative CPCs. Results were not linked to endothelial matrix remodeling or CPC mobilization. These results provide information to better understand the endothelium and immature immune system during an active, short-term sojourn at high altitude.